Trajectories and associations between wearable-derived mobility, patient-reported outcomes, clinical measures and clinical indicators following total knee arthroplasty: The IMPACT project protocol - Daniel Hickey; Rory Lambe; Quentin Le Cornu; Anthony Pierce; Ian Byrne; Cailbhe Doherty; Brian Caulfield (PLoS ONE, 2026)
Background Total Knee Arthroplasty (TKA) is one of the most frequently performed elective surgical procedures worldwide. In the United States, annual procedure volumes are projected to exceed 3.5 million by 2030, while demand in Ireland is expected to rise by 49% by 2036. Despite its overall effectiveness, up to 20% of patients remain dissatisfied post-operatively. Conventional follow-up methods rely on intermittent Patient-Reported Outcome Measures (PROMs) and clinic-based performance tests, which provide only a partial view of recovery. Wearable-derived mobility data offers the opportunity to capture daily activity patterns in free-living conditions, complementing PROMs and clinical assessments to refine understanding of recovery trajectories following TKA. Methods This prospective observational cohort study will recruit up to 160 participants scheduled for unilateral TKA at the Beacon Hospital (Dublin, Ireland). Participants will wear a Garmin Vivosmart 5 continuously from up to four weeks pre-operatively to 6 months post-operatively. Continuous, minute-level wearable data will be collected including daily step count. PROMs will be collected using the Labfront Companion mobile application and will include weekly numeric ratings of pain, fatigue, stiffness and sleep quality; the Oxford Knee Score (OKS) at 30-day intervals; and the EQ-5D-5L at 60-day intervals. Clinical indicators and measures will be abstracted from the electronic health record (Meditech). Clinical and demographic measures include age, sex, height, weight, body mass index (BMI), and participation in prehabilitation exercise classes. Primary statistical analysis will evaluate longitudinal trend analysis of step count and PROMs over time after surgery, while covariate-adjusted Spearman-type correlations will evaluate cross-sectional associations between daily step count, OKS, EQ-5D-5L and pain. Expected outcomes This study will characterise wearable-derived mobility metrics across early and mid-stage recovery following TKA, and evaluate their associations with PROMs. Conclusions Integrating continuous wearable data with PROMs and clinical information may refine post-operative monitoring and support personalised rehabilitation following TKA.